2016
DOI: 10.1111/jace.14234
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Effects on Microstructure Formation During FLASH Sintering of Yttrium‐Stabilized Zirconia

Abstract: Systematic microstructural statistics for 3 mol% yttria-stabilized zirconia synthesized by both conventional sintering and flash sintering with AC and DC current were obtained. Within the gage section, flash sintered microstructures were indistinguishable from those synthesized by conventional sintering procedures. With both techniques, full densification was obtained. However, from both AC and DC flash sintered specimens, heterogeneous grain size distributions and residual porosity were observed in the proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 36 publications
4
93
0
5
Order By: Relevance
“…There is evidence that the handle-sections of flash-sintered dogbone specimens experience higher electric fields and hence higher temperatures, leading to larger grain growth under DC electric fields [41]. This means that in practice, were the samples to be used for further applications, these sections would need to be removed.…”
Section: Specimen Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that the handle-sections of flash-sintered dogbone specimens experience higher electric fields and hence higher temperatures, leading to larger grain growth under DC electric fields [41]. This means that in practice, were the samples to be used for further applications, these sections would need to be removed.…”
Section: Specimen Geometrymentioning
confidence: 99%
“…This means that in practice, were the samples to be used for further applications, these sections would need to be removed. It has also been suggested that drilling holes into the ceramic dogbone samples in the green state for electrode wires can introduce damage [41].…”
Section: Specimen Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…According to their analysis the application of an electric field contributed to the creation and segregation of vacancies [70] at the boundaries reducing the rate of grain growth. Their analysis did not account for polarity induced effects described in Qin et al [74] and Kim et al [116]. The proposed mechanism for grain growth retardation in AC are described by Conrad and Wang [146].…”
Section: Self-constitutive Modelling Of Densification Kinetics and Grmentioning
confidence: 99%
“…Ionic conductors. It is worth noting that in the AC mode, Pt electrodes are blocking [74]. In DC, the two identified effects are the enhanced grain growth at the cathode site and electrochemical reduction of the material.…”
Section: Polarity Induced Effectsmentioning
confidence: 99%